Patient doses and occupational exposure in a hybrid operating room. (May 2017) - Andrés, C.; Pérez-García, H.; Agulla, M.; Torres, R.; Miguel, D.; del Castillo, A.; Flota, C.M.; Alonso, D.; de Frutos, J.; Vaquero, C.
Highlights: The radiation protection carried out in the first year of use of an HOR dedicated to vascular surgery was evaluated. Working conditions in the HOR are safe regarding patient and staff radiation protection. Patient doses are comparable to those resulting from other endovascular dose studies. Annual dose limit to the exposed professionals were not exceeded during the study. Abstract: Purpose: This study aimed to characterize the radiation exposure to patients and workers in a new vascular hybrid operating room during X-ray-guided procedures. Methods: During one year, data from 260 interventions performed in a hybrid operating room equipped with a Siemens Artis Zeego angiography system were monitored. The patient doses were analysed using the following parameters: radiation time, kerma-area product, patient entrance reference point dose and peak skin dose. Staff radiation exposure and ambient dose equivalent were also measured using direct reading dosimeters and thermoluminescent dosimeters. Results: The radiation time, kerma-area product, patient entrance reference point dose and peak skin dose were, on average, 19:15 min, 67 Gy·cm 2, 0.41 Gy and 0.23 Gy, respectively. Although the contribution of the acquisition mode was smaller than 5% in terms of the radiation time, this mode accounted for more than 60% of the effective dose per patient. All of the worker dose measurements remained below the limits established by law. Conclusions: The working conditions in the hybrid operating room HOR are safe in terms of patient and staff radiation protection. Nevertheless, doses are highly dependent on the workload; thus, further research is necessary to evaluate any possible radiological deviation of the daily working conditions in the HOR.